Sulṭat al-Ijmāʿ: Jadaliyyat al-Shukūkiyyah wa-Ḥasm al-Juwaynī - Ali Mahrus Fuad; Ghilmanul Wasath; Muhammad Khairul Mustaghfirin; Zuhratul Aini Mansur (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study examines the authority of ijmāʿ as a definitive principle in Islamic legal theory within the framework of the dialectics of skepticism that emerged in the classical period—most notably in the thought of certain theologians such as al-Naẓẓām al-Muʿtazilī—and has been revived in contemporary approaches that question either the possibility of ijmāʿ or its methodological binding force. The study aims to analyze the epistemological and theological roots of such skepticism and to elucidate how Imam al-Juwaynī (d. 478 AH) provided a decisive methodological resolution by constructing a coherent uṣūlī framework for the authority of ijmāʿ, as articulated in his works al-Burhān and al-Talkhīṣ. Employing a descriptive-analytical methodology grounded in a critical uṣūlī approach, the study analyzes al-Juwaynī’s texts and compares his arguments with those of classical and contemporary skeptics. The findings demonstrate that modern skepticism does not constitute an epistemic rupture but rather represents a direct extension of earlier uṣūlī objections. The study further shows that al-Juwaynī’s key contribution lies in establishing the definitive nature (qaṭʿiyyah) of ijmāʿ through the principle of “consistency of customary practice” (iṭrād al-ʿādah) as an epistemological intermediary that elevates ijmāʿ from a conjectural textual proof to methodological certainty. The novelty of this study resides in demonstrating that al-Juwaynī’s approach offers a systematic and conclusive uṣūlī model capable of addressing all forms of skepticism, both classical and contemporary.